Development of Early Detection Assessment Questionnaire for Type 2 Diabetes Mellitus for Health Cadres - Fuji Rahmawati; Herliawati Herliawati; Firnaliza Rizona (Indonesian Journal of Global Health Research, 2025)
In 2021 Diabetes Mellitus (DM) type 2 contributes to more than 90% of the total diabetes cases globally, which means more than 482.94 million individuals suffer from this disease. This figure is believed to be higher because there are still many residents who have not been detected. In Indonesia, early detection of type 2 DM is integrated with the Posbindu program, but it is still not running optimally because there is no instrument that can identify high-risk community groups. Objective: This study aims to design an early detection assessment questionnaire for type 2 DM that can be used by health cadres. Method: This study used research and development method. According of the 10 steps of the research and development method, researchers only used 9 steps due to environmental conditions, limited time and research costs. The product that will be produced in this research is an early detection assessment instrument in the form of a questionnaire consisting of questions related to signs and symptoms as well as risk factors for type 2 DM. The population consists of people in the working area of the Puskesmas Simpang Timbangan. The data analysis technique used during product testing is validity testing using Pearson product moment and reliability testing using Cronbach's alpha with validity value r count > r table (0.3008) and reliability value 0.746 (> 0.60). Results: From the development of the questionnaire, 15 closed questions were obtained that were valid and reliable for use. Conclusions: This early detection assessment questionnaire can be used by health cadres in early detection of risk factors for DM Type 2 in the community.